Programming of Vascular Dysfunction by Maternal Stress: Immune System Implications - Costa, Tiago J.; De Oliveira, Júlio Cezar; Giachini, Fernanda Regina; Lima, Victor Vitorino; Tostes, Rita C.; Bomfim, Gisele Facholi (Frontiers in Physiology, 2022)
A growing body of evidence highlights that several insults during pregnancy impact the vascular function and immune response of the male and female offspring. Overactivation of the immune system negatively influences cardiovascular function and contributes to cardiovascular disease. In this review, we propose that modulation of the immune system is a potential link between prenatal stress and offspring vascular dysfunction. Glucocorticoids are key mediators of stress and modulate the inflammatory response. The potential mechanisms whereby prenatal stress negatively impacts vascular function in the offspring, including poor hypothalamic-pituitary-adrenal axis regulation of inflammatory response, activation of Th17 cells, renin-angiotensin-aldosterone system hyperactivation, reactive oxygen species imbalance, generation of neoantigens and TLR4 activation, are discussed. Alterations in the immune system by maternal stress during pregnancy have broad relevance for vascular dysfunction and immune-mediated diseases, such as cardiovascular disease.